Peran NU dan Muhammadiyah dalam transformasi Pendidikan di Indonesia - Wifaqi, Hikmah (Maliki Interdisciplinary Journal, 2025)
This article highlights the roles of Nahdlatul Ulama (NU) and Muhammadiyah in education in Indonesia, reviewing aspects such as educational concepts, goals, impacts, innovations, and implementation of Islamic values. NU focuses on education that promotes Aswaja values, emphasizing adab, as well as morals, with the aim of forming moderate and tolerant individuals. NU education through pesantren and madrassas maintains the Nusantara Islamic tradition while adapting to modernity. In contrast, Muhammadiyah emphasizes a balance between religious and general sciences and holistic education that involves family and community. By adopting modern educational approaches and integrating knowledge, Muhammadiyah aims to create individuals who are intelligent and have good morals, and are able to face the challenges of the times. Both play a major role in shaping a moderate and responsive generation, while enriching the Indonesian education system with adaptive and innovative Islamic values.